(untitled) (UNWE Yearbook, 2024)
The subject matter of this article is the green technology and its protection as intellectual property objects, more particularly as invention. The analysis will focus on green technology in agriculture and the economic development of the countries over the last two decades due to these technologies. The article indicates the essence of green technologies and the areas of application of the technology, mainly in agriculture. A profile of the enterprises developing green technologies has been made. The results of the performed patent research are analysed, and the top applicants/owners of patents are identified. The filed national and international applications for inventions and the issued patents in the field of green technologies are deduced on country/territory bases. The Influence of green technologies on the development of new plant varieties is also analysed. The thesis of the present study is that one of the important factors for achieving and maintaining economic development and competitiveness of enterprises in today’s competitive environment is the creation of innovative products in the field of green technology and their protection as a patent for an invention.